Hubungan Pendapatan dan Sikap terhadap Keberhasilan Menyusui Eksklusif - Rika Ruspita; Rifa Rahmi; Komaria Susanti (Poltekkes Kemenkes Palu, 2023)
Introduction: The success rate of Exclusive Breastfeeding (EBF) in Indonesia is recorded at 66.1%. The province of Riau has achieved a success rate of 78% for EBF, indicating that both nationally and in the province of Riau, the target of EBF has been exceeded by 40%. Income and attitude influence the provision of exclusive breastfeeding. Objective: To determine the relationship between income and attitude towards the success of exclusive breastfeeding among mothers of infants aged 7-12 months. Methods: This study employed a quantitative approach with a descriptive analytic design. The research was conducted in the Rejosari Pekanbaru Primary Health Care Working Area for four months in June 2022. The sample consisted of 38 mothers with infants aged 7-12 months. The independent variables were income and attitude, while the dependent variable was the success of exclusive breastfeeding. Results: The analysis revealed that there was a relationship between family income and the success of exclusive breastfeeding, with 77.3% of mothers with low income successfully practicing EBF. Similarly, a relationship was found between attitude and the success of exclusive breastfeeding, with 77.3% of mothers having a positive attitude towards EBF. The statistical analysis showed a significant relationship between income (p=0.032), attitude (p=0.032), and the success of exclusive breastfeeding. Conclusion: There is a relationship between income, attitude, and the success of exclusive breastfeeding. This study suggests that healthcare professionals should provide education and counseling on the importance of exclusive breastfeeding to breastfeeding mothers to achieve EBF.